2010
DOI: 10.1177/0961203310377219
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplantation in systemic lupus erythematosus: case report and review of the literature

Abstract: Severe liver involvement requiring liver transplantation is a rare complication in systemic lupus erythematosus (SLE), but very few cases have been reported. We describe a 39-year-old woman with SLE who underwent successful liver transplantation due to acute liver failure. The patient persisted without reactivation of SLE and with good long-term survival. Management and diagnosis considerations are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…There are few reports of liver transplants in patients with SLE. 85 These have few patients with diseases not related to SLE as indications for transplantation and generally obtaining favourable results with complications not related to SLE. In addition, immunosuppressive medications to prevent graft rejection are usually sufficient to suppress SLE activity.…”
Section: Treatment Of Liver Diseases In Slementioning
confidence: 99%
“…There are few reports of liver transplants in patients with SLE. 85 These have few patients with diseases not related to SLE as indications for transplantation and generally obtaining favourable results with complications not related to SLE. In addition, immunosuppressive medications to prevent graft rejection are usually sufficient to suppress SLE activity.…”
Section: Treatment Of Liver Diseases In Slementioning
confidence: 99%
“…Severe liver involvement requiring liver transplantation in SLE, but very few cases have been reported. The patient persisted without reactivation of SLE and with long-term survival (10) .…”
Section: Introductionmentioning
confidence: 82%
“…Barthel et al first reported the use of liver transplantation in three patients with SLE; two did very well, and one experienced hyperacute rejection [ 28 ]. Lian EC et al and F Zazzetti et al each reported a patient with SLE; both patients underwent transplantation because of liver failure, did not have SLE reactivation and had good long-term survival [ 33 , 34 ]. These reports show that patients with SLE are capable of undergoing liver transplantation without experiencing SLE reactivation and have good long-term survival.…”
Section: Discussionmentioning
confidence: 99%